The Effects of Light Treatments on Growth and Flowering Characteristics of Oncidesa Gower Ramsey ‘Honey Angel’ at Different Growth Stages - Chia-Man Chang; Ching-Wen Wang; Meng-Yuan Huang; Chung-I Chen; Kuan-Hung Lin; Chih-Pei Shen (Agriculture, 2023)
In our previous work, we observed that Oncidesa Gower Ramsey ‘Honey Angel’ (HA) plants became stunned on hot summer afternoons, and the seasonal trend in solar radiation affected its production schedule by limiting flower yield and quality. The objective of this work was to study the growth and flowering characteristics of HA pseudobulbs at three stages of growth (G2–G4) in response to three types of light-emitting diode (LED) lighting treatments, including full spectrum (FS), deep red/white-medium blue (DR/W-MB), and deep red/white-low blue (DR/W-LB), for two additional time intervals. The supplementary LED lighting time intervals (S) applied daily were carried out for 1 h (4:00~5:00 a.m., as S-1) or 2 h (4:00~6:00 a.m., as S-2) from March to September, 2022. Natural light without supplemental lighting was the control. The length of pseudobulb (PL), width of pseudobulb (PW), thickness of pseudobulb (PT), length of inflorescence (FL), number of branches (FB), number of florets (FN), and days to flowering (FD) per plant were recorded andcalculated when 80% of florets became mature. Light treatments significantly affected all pseudobulb growth and flower quality traits at different Gs, especially pseudobulb length (PL) and flower number (FN) under different LED types and lighting time intervals. MB-1 treatment promoted PT at both G3 and G4, whereas MB-2 treatment increased PW at both G2 and G4. Both MB-1 and LB-1 treatments had augmented effects on PL, respectively, at G2 and G3. The PW, FL, FB, and FN increased with additional light time and reached maxima under MB-2 treatment at G4 compared to other treatments and controls. Early flowering and an increased number of flowers at G4 were observed in plants grown under MB-2 treatment. Controlling light quality and supplementary light time intervals enables the production of HA plants with the desired growth and flowering quality characteristics of the pseudobulbs.